Core decompression combined with implantation of a demineralised bone matrix for non-traumatic osteonecrosis of the femoral head - Helbig, Lars; Schmidmaier, Gerhard (Archives of orthopaedic and trauma surgery, 2012)
Introduction: Core decompression is the standard surgical procedure in the treatment of early stage non-traumatic osteonecrosis of the femoral head (ONFH). However, there is still a debate whether decompression in combination with supplementary augmentation by bone grafts, growth factors, or cell implementation is superior to conventional decompression alone. This study evaluated patients after core decompression combined with an augmentation by a demineralised bone matrix, and particularly aimed to report long-term conversion rates to total hip replacement (THR). Materials and methods: 14 patients with 18 hips suffering from ONFH (Ficat stage I-IIB) underwent this surgical procedure. All patients underwent radiographic and MRI investigations at baseline and at follow-up periods of 12 and 24 months. The clinical follow-up was done using the Merle d’Aubigné-score for an average period of 9 years after surgery. Results: 14 of the 18 subjects (77 %) achieved at least a good clinical result after 2 years. The Merle d’Aubigné-score improved significantly after 12 (p = 0.0001) and 24 months (p = 0.0002). However, the MRI volumetric analysis showed an increased necrotic bone volume from 3.16 ± 0.54 to 3.88 ± 0.62 cm3 (p = 0.04). Within 9 years, 13 out of 18 cases (72 %) required further surgery by THR. Only 7 out of 18 subjects (39 %) reported an ongoing postoperative clinical benefit, and would retrospectively redo the same surgical approach again. The five patients that did not require THR were still satisfied after 9 years. Conclusions: In patients with early-stage femoral head osteonecrosis core decompression combined with the implantation of a demineralised bone matrix leads to a limited, temporary pain relief as seen in core decompression alone. However, long-term results were not encouraging with a high rate of conversion to arthroplasty. Therefore, core decompression with implantation of a demineralised bone matrix may be not appropriate to avoid THR in the long term.